Cynomolgus monkey model of interleukin‐31‐induced scratching depicts blockade of human interleukin‐31 receptor A by a humanized monoclonal antibody. Issue 1 (10th April 2017) - Oyama, Sohei; Kitamura, Hidetomo; Kuramochi, Taichi; Higuchi, Yoshinobu; Matsushita, Hiroaki; Suzuki, Tsukasa; Goto, Masaaki; Adachi, Hideki; Kasutani, Keiko; Sakamoto, Akihisa; Iwayanagi, Yuki; Kaneko, Akihisa; et al.
Abstract: Scratching is an important factor exacerbating skin lesions through the so‐called itch‐scratch cycle in atopic dermatitis (AD). In mice, interleukin (IL)‐31 and its receptor IL‐31 receptor A (IL‐31RA) are known to play a critical role in pruritus and the pathogenesis of AD; however, study of their precise roles in primates is hindered by the low sequence homologies between primates and mice and the lack of direct evidence of itch sensation by IL‐31 in primates. We showed that administration of cynomolgus IL‐31 induces transient scratching behaviour in cynomolgus monkeys and by that were able to establish a monkey model of scratching. We then showed that a single subcutaneous injection of 1 mg/kg nemolizumab, a humanized anti‐human IL‐31RA monoclonal antibody that also neutralizes cynomolgus IL‐31 signalling and shows a good pharmacokinetic profile in cynomolgus monkeys, suppressed the IL‐31‐induced scratching for about 2 months. These results suggest that the IL‐31 axis and IL‐31RA axis play as critical a role in the induction of scratching in primates as in mice and that the blockade of IL‐31 signalling by an anti‐human IL‐31RA antibody is a promising therapeutic approach for treatment of AD. Nemolizumab is currently under investigation in clinical trials.